LearningSpace: problems and experiences - Kulvietienė, Regina; Šileikienė, Irma (Lietuvos matematikos rinkinys, 2001)
To be successful in times of turbulence and constant change, organizations need people who are flexible, teamworkers, good communicators and constant learners. Many organizations have recognized the key role that training can play in delivering this type of workforce. In order to respond to this challenge, training departments must look at new methods and techniques. In Virtual University, much emphasis has been given to the pedagogical concepts of student centered learning and student motivation, resulting in the design and delivery of high quality courses in higher education as well as more generally in resource based education. E-business solutions. Executives in higher education are challenged with maintaining and enhancing academic quality, maintaining or increasing student enrollment, recruiting and training faculty members, raising funds, and maintaining financial performance. A complete solution for higher education would intėgrate these processes and deliver support to campus constituents through Web-enabled services.